Analisis Dukungan Keluarga Terhadap Perilaku Ibu Dalam Perawatan Kehamilan Di Bpm Restu Ibu Sragen - Widy Nurwiandani; Ari Andriyani (Sekolah Tinggi Ilmu Kesehatan Akbidyo, 2021)
ABSTRACTBackground: Maternal death in the reproductive process is a worrying tragedy, because the presence of a mother is the main milestone for achieving a prosperous family and the death of a mother is a disaster for her family2. For this reason, the mother's attitude in preventing pregnancy complications or to reduce pregnancy complications early is to carry out routine checks according to the recommendations of health workers (Doctors, Midwives). So that mothers, husbands and families can find out as soon as possible how to prevent pregnancy complications and if there are problems that arise in pregnancy3. Mortality and morbidity in pregnant women is a major problem in developing countries. In poor countries around 25-50%. The death of fertile women is caused by things related to pregnancy. Death during childbirth is usually a major factor in the mortality of young women at their peak of productivity. In 1996 WHO (Word Health Organization) estimated that more than 585,000 mothers per year died during pregnancy or childbirth, actually more than 50% of deaths in 2 developing countries. The deaths of pregnant women in Indonesia are bleeding, infection and eclampsia, besides that, deaths due to abortion and prolonged labor are also included. About 50% of maternal deaths are caused by diseases that worsen due to pregnancy, such as heart disease and chronic infections. The results of a preliminary study of 10 pregnant women regarding family support for prenatal care, it turns out that there are still 80% (8 people) pregnant women get very good support from their husbands and families, while 20% (2 people) pregnant women get a lot of support from their husbands. as well as family. Objective : To find out family support for the behavior of pregnant women in pregnancy care at BPM Restu Ibu Sragen. Methods : This research was conducted at BPM Restu Ibu Sragen in August 2021. The research design used univariate correlation with this research design using cross sectional.Results : By using the Chi-Square formula and the contingency coefficient, it was found that 53.3% of pregnant women received support from their families and 60% of pregnant women did not regularly perform prenatal care. The results of the cross tabulation between family support and maternal behavior in pregnancy care showed that 40% of pregnant women who did not receive family support behaved irregularly in pregnancy care, with the results of x2 count = 7.22 and x2 table = 3.84 where x2 count > x2 table with a significant level of 0.05. Conclusion: There is a relationship between family support and maternal behavior in pregnancy care at BPM Restu Ibu Sragen. Keywords: Family Support, Behavior of Pregnant Women